Հյուսիսատլանտյան դաշինքի կազմակերպության ռազմավարական հայեցակարգերի փոխակերպման առանձնահատկությունները - Ղևոնդյան, Ալեն (YSU Journal of International Affairs, 2017)
The article is devoted to the conceptual transformation and subsequent expansion of the activities of the North Atlantic Treaty Organization after the end of the Cold War. A comparative analysis of the three Strategic Concepts of the North Atlantic Alliance of 1991, 1999 and 2010 is conducted.
Keywords: NATO, transformation, strategic concept, collective security system